Belicinus Rhomboideus, a new genus and species of Psepheninae (Coleoptera: Byrrhoidea: Psephenidae) from Belize - Arce-Pérez, Roberto; Shepard, William D.; Morón, Miguel A. (Zootaxa, 2012)
Belicinus rhomboideus gen. nov., sp. nov. is described and illustrated based on specimens collected in Belize. Belicinusgen. nov. can be distinguished from other Psepheninae genera by the following characteristics: pronotal shape, tibiae andtarsomeres (Psephenus, Psephenops); antennae, tibiae, tarsomeres and phallobase (Pheneps); antennae, pronotum and tib-iae (Psephenotarsis); maxillary palpi and tibiae (Psephenopalpus). Belicinus appears to be more closely related to Pse-phenotarsis than to other Psepheninae genera. The larvae and habitat are described. A key for American Psepheninae genera is provided.